2021
DOI: 10.3171/2019.12.jns192744
|View full text |Cite
|
Sign up to set email alerts
|

Age dependency and modification of the Subarachnoid Hemorrhage Early Brain Edema Score

Abstract: OBJECTIVEThe Subarachnoid Hemorrhage Early Brain Edema Score (SEBES) system measures cerebral edema on CT and can be used to predict outcome after subarachnoid hemorrhage (SAH). The authors developed a modified SEBES (SEBES 6c) and assessed whether it could predict outcome after SAH better than the SEBES. Furthermore, they verified the age dependency of these scores.METHODSIn this retrospective study, all … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…EBI is important as it reflects that the initial clinical presentation is the most important predictor of outcome 34 . It is reported that SEBES is associated with clinical markers of EBI, such as HH and WFNS, and is an independent predictor of DCI and poor short‐term and long‐term clinical outcomes 11,35 . Furthermore, WFNS and SEBES simply reflect the aggravated brain injury related to the severity of the initial bleed, and exerted their predictive effects in AN‐SAH assessment than the other clinical scales.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…EBI is important as it reflects that the initial clinical presentation is the most important predictor of outcome 34 . It is reported that SEBES is associated with clinical markers of EBI, such as HH and WFNS, and is an independent predictor of DCI and poor short‐term and long‐term clinical outcomes 11,35 . Furthermore, WFNS and SEBES simply reflect the aggravated brain injury related to the severity of the initial bleed, and exerted their predictive effects in AN‐SAH assessment than the other clinical scales.…”
Section: Discussionmentioning
confidence: 99%
“… 34 It is reported that SEBES is associated with clinical markers of EBI, such as HH and WFNS, and is an independent predictor of DCI and poor short‐term and long‐term clinical outcomes. 11 , 35 Furthermore, WFNS and SEBES simply reflect the aggravated brain injury related to the severity of the initial bleed, and exerted their predictive effects in AN‐SAH assessment than the other clinical scales. In our present study, the nomograms were constructed based on symptomatic vasospasm, WFNS, SEBES, and bleeding pattern to facilitate a quantitative assessment of disability for individual patients once their clinical and imaging data were available.…”
Section: Discussionmentioning
confidence: 99%
“…Only one previous study reported age as a predictor of EBE severity. Eibach et al [9] described higher SEBES (3–4) in patients younger than 60 years in a cohort of 261 patients.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the SEBES has previously been proven accurately to predict delayed cerebral edema in SAH patients [7,8]. Recently, Eibach et al [9] demonstrated that SEBES predicts outcome and delayed cerebral ischemia independently of vasospasm. The association between SEBES and functional outcome after SAH has also been shown in previous studies [8].…”
Section: Sebes: a Reliable Marker Of Ebe?mentioning
confidence: 99%
See 1 more Smart Citation